Fintech and financial literacy in Viet Nam - Peter J. Morgan; Long Quang Trinh (Asian Development Bank Institute (ADBI), 2020)
Financial literacy is gaining increasing importance as a policy objective in many countries. A growing literature has examined the role of financial literacy in an individual's income, saving behavior, and the use of various financial products. However, so far, we are not aware of any studies of the relationship between financial literacy and the awareness and adoption of financial technology (fintech) products, i.e., financial products provided via internet-based and mobile-based platforms especially in developing countries. This paper examines this relationship in a developing country, Viet Nam. To do so, we conducted a survey on financial literacy and fintech awareness and adoption, using financial literacy questions to calculate a financial literacy score. We find that a higher level of financial literacy has strong and positive effects on an individual's awareness and use of fintech products.
Keywords: D14; G11; J26; 330; financial literacy; financial behavior; fintech; awareness of fintech; household saving; Viet Nam